El juego como herramienta terapéutica en las dificultades emocionales de niños de 4 a 5 años de edad en la unidad educativa “Verbo Divino”, provincia Bolívar, cantón Guaranda, periodo 2024 - Núñez Castro, Doris Nicol (2025)
Talking about play is important in education, it is a natural and fundamental activity for child development, play transcends beyond fun, it is a medium where children learn, explore and understand the world through the environment that surrounds them. The game promotes the ability to solve problems and contributes positively to infants to shape their personality. As the child grows, the game evolves. The game is not limited to fun, meaningless activities, but uses various strategies to teach important concepts and skills, for example, you can use classification games to teach mathematics or vocabulary games to teach language, where instead that the child memorizes mechanically, through which significant and lasting learning is achieved. Play therapy is a therapeutic method that uses play as a means of communication and expression for children. Through toys, role-playing, creative activities, and other forms of play, children can explore their emotions, thoughts, and experiences in a safe, non-threatening way.